Responses of the alga Pseudokirchneriella subcapitata to long-term exposure to metal stress - Machado, Manuela D. (2016)
The green alga Pseudokirchneriella subcapitata has been widely used in ecological risk assessment, usually based on the impact of the toxicants in the alga growth. However, the physiological causes that lead algal growth inhibition are not completely understood. This work aimed to evaluate the biochemical and structural modifications in P. subcapitata after exposure, for 72 h, to three nominal concentrations of Cd(II), Cr(VI), Cu(II) and Zn(II), corresponding approximately to 72 h-EC10 and 72 h-EC50 values and a high concentration (above 72 h-EC90 values). The incubation of algal cells with the highest concentration of Cd(II), Cr(VI) or Cu(II) resulted in a loss of membrane integrity of ~16, 38 and 55%, respectively. For all metals tested, an inhibition of esterase activity, in a dose-dependent manner, was observed. Reduction of chlorophyll a content, decrease of maximum quantum yield of photosystem II and modification of mitochondrial membrane potential was also verified. In conclusion, the exposure of P. subcapitata to metals resulted in a perturbation of the cell physiological status. Principal component analysis revealed that the impairment of esterase activity combined with the reduction of chlorophyll a content were related with the inhibition of growth caused by a prolonged exposure to the heavy metals.